Karakteristik Produk Bordir Berdasarkan Kepuasan Konsumen Segala Rintisan Pemberdayaan Sentra Industri Kecil Di Jawa Timur (Studi Kasus Di Sentra Industri Kecil Bordir Tanggulangin Sidoarjo) - Jun Surjanti, (Bisnis dan Manajemen, 2009)
Sidoarjo has been known as the center of SMEs. As for embroidery product, price variable is the most dominant variable. The research that will be conducted is based on the previous research that has been conducted by the researchers regarding the customer perception of the characteristics of embroidery product. This research is an exploratory research. The research method that will be used is qualitative descriptive which will be quantified by Quality Function Deployment method. The Subject of this research is the customers, embroidery experts, and TTG experts. The results of the survey consists of data regarding the customer expectation on embroidery products in 4 (four) embroidery outlets in Sidoarjo. The data collected is arranged into the customer quality demand which subsequently comprised into the construct of quality performance. Afterward, the data is processed using WELCOME program and applied into an electric embroidery machinem which could produce formatted embroidery pattern. Embroidery patterns that are desired by customers are flowery type such as jasmine, rose, cherry blossom, and KAMBOJA with size in a range of 1-3 cm, which is located in a variety of places, using KESET technique, and modified into 2 dimension with beads, and the color that is preferred is secondary color such as orange, violet, and green, and the type of fabrics that is favored is cotton. In term of the technological capability that is possessed by the crafter, all demand for the customer quality construct can be satisfied. This is possible because a meeting regarding the capability and competence of the crafter has been arranged before the survey was conducted. All crafter that is surveyed in embroidery pattern and process is still manual without the use of computerized machine with embroidery pattern software.